Cultural competence in America's schools : leadership, engagement and understanding - Jones, Bruce Anthony; Nichols, Edwin J. (Emerald Publishing Limited : Information Age Publishing, 2013)
"Focuses on explicating the impact of culture and issues of race and ethnicity on student learning, teacher and leadership efficacy, and educational policy making in our nation's public school system"--Back cover.
Keywords: Teaching -- United States.; Cultural competence.; Public schools -- United States -- Cultural policy.; Multicultural education -- United States.; Teaching.; United States.; Education -- Teaching -- General.; Teaching skills and techniques.; elektronické knihy; electronic books